Chuj (Mayan) narratives : folklore, history, and ethnography from northwestern Guatemala - Hopkins, Nicholas A. (University Press of Colorado, 2021)
"Analyzes six narratives that illustrate the breadth of the (relatively isolated) Mayan Chuj storytelling tradition, from ancient mythology to current events and from intimate tales of local affairs to borrowed stories"--